COVID-19 Testing Among US Children, Parental Preferences for Testing Venues, and Acceptability of School-Based Testing. (March 2022) - Teasdale, Chloe A.; Borrell, Luisa N.; Shen, Yanhan; Kimball, Spencer; Rinke, Michael L.; Rane, Madhura S.; Kulkarni, Sarah; Fleary, Sasha A.; Nash, Denis
Objectives: Testing remains critical for identifying pediatric cases of COVID-19 and as a public health intervention to contain infections. We surveyed US parents to measure the proportion of children tested for COVID-19 since the start of the pandemic, preferred testing venues for children, and acceptability of school-based COVID-19 testing. Methods: We conducted an online survey of 2074 US parents of children aged ≤12 years in March 2021. We applied survey weights to generate national estimates, and we used Rao–Scott adjusted Pearson χ 2 tests to compare incidence by selected sociodemographic characteristics. We used Poisson regression models with robust SEs to estimate adjusted risk ratios (aRRs) of pediatric testing. Results: Among US parents, 35.9% reported their youngest child had ever been tested for COVID-19. Parents who were female versus male (aRR = 0.69; 95% CI, 0.60-0.79), Asian versus non-Hispanic White (aRR = 0.58; 95% CI, 0.39-0.87), and from the Midwest versus the Northeast (aRR = 0.76; 95% CI, 0.63-0.91) were less likely to report testing of a child. Children who had health insurance versus no health insurance (aRR = 1.38; 95% CI, 1.05-1.81), were attending in-person school/daycare versus not attending (aRR = 1.67; 95% CI, 1.43-1.95), and were from households with annual household income ≥$100 000 versus income <$50 000-$99 999 (aRR = 1.19; 95% CI, 1.02-1.40) were more likely to have tested for COVID-19. Half of parents (52.7%) reported the pediatrician's office as the most preferred testing venue, and 50.6% said they would allow their youngest child to be tested for COVID-19 at school/daycare if required. Conclusions: Greater efforts are needed to ensure access to COVID-19 testing for US children, including those without health insurance.